Understanding resistance to childhood vaccination in the UK: radicals, reformists and the discourses of risk, trust and science - Hobson-West, Pru (2005)
Vaccination is regarded by the medical profession as one of the greatest public health success stories, and recent opposition, for example over the MMR (measles, mumps and rubella) vaccine, as a failure of understanding. Relatively little social scientific analysis exists on vaccination opposition. However, risk, trust and science are dominant themes within literature on public resistance to technology, and in contemporary theories such as risk society. This thesis therefore evaluates the relevance of these themes for an understanding of vaccination resistance in the UK. The empirical research primarily involves a discourse analysis of interview, document and website data generated from ten parental organisations, established to campaign against aspects of vaccination policy. The study defines these organisations as 'Vaccine Critical groups' and further classifies them into Radical and Reformist categories.